THEORETICAL FUNDAMENTALS OF SPORTS EXERCISES - Uraimov Sanjar; Tillaev Sharifjon (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In this article , the main goal of the reforms being carried out in Uzbekistan is to create a healthy and well-educated generation in our country with high spiritual and moral qualities. Because physical education and sports play an important role in the growth and healthy development of young people. A healthy person develops self-confidence, perseverance, skills and qualities of being able to finish what he has started. The article examines sports activities.